2019
DOI: 10.1038/s41598-019-42391-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial disease induced changes in fungal communities of olive tree twigs depend on host genotype

Abstract: In nature, pathogens live and interact with other microorganisms on plant tissues. Yet, the research area exploring interactions between bacteria-fungi and microbiota-plants, within the context of a pathobiome, is still scarce. In this study, the impact of olive knot (OK) disease caused by the bacteria Pseudomonas savastanoi pv. savastanoi (Psv) on the epiphytic and endophytic fungal communities of olive tree twigs from three different cultivars, was investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 50 publications
4
39
0
1
Order By: Relevance
“…Although there are still gaps in understanding the dynamism and complexity of such metabolic alterations 23 , recent studies have indicated that this response is cultivar dependent 24 . Our hypothesis is further reinforced by the Varpart analysis, which showed a greater contribution of host cultivar to the bacterial assemblage in OK-symptomatic twigs (24.4%) when compared to asymptomatic twigs (2.5%), as similarly observed for the fungal community in the same olive tree cultivars 16 . The role of host plant in structuring both rhizosphere and root endosphere bacterial communities in response to a pathogen www.nature.com/scientificreports www.nature.com/scientificreports/ attack was already reported 25,26 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although there are still gaps in understanding the dynamism and complexity of such metabolic alterations 23 , recent studies have indicated that this response is cultivar dependent 24 . Our hypothesis is further reinforced by the Varpart analysis, which showed a greater contribution of host cultivar to the bacterial assemblage in OK-symptomatic twigs (24.4%) when compared to asymptomatic twigs (2.5%), as similarly observed for the fungal community in the same olive tree cultivars 16 . The role of host plant in structuring both rhizosphere and root endosphere bacterial communities in response to a pathogen www.nature.com/scientificreports www.nature.com/scientificreports/ attack was already reported 25,26 .…”
Section: Discussionsupporting
confidence: 76%
“…Thus, the olive cultivar seems to influence the establishment of pathobiome communities in olive knots. Accordingly, previous studies have suggested that differences on microbial abundance and diversity between asymptomatic and symptomatic tissues were possibly related to the susceptibility of the plant host to a certain disease 16,[18][19][20][21] . We hypothesized that the detected greater differences in the bacterial composition of OK-susceptible cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of fungal endophyte communities in olive were mainly performed in aboveground organs by using cultivation-dependent methods [ 42 , 43 , 44 , 45 ], while metabarcoding analysis was less frequently used. All these studies indicated Ascomycota as the most abundant fungal endophytes in olive leaves, twigs, and fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria and fungi naturally coexist in various environments, and their cooperation or antagonistic interactions are widely demonstrated for humans, plants, aquatic and soil ecosystems and signi cantly impact their functions (Das et al, 2012;Gomes et al, 2019). Since soil bacteria and fungi are the major components of soil ecosystems, exploration of the bacterial and fungal community diversities and compositions and their co-exist patterns in different sizes of spatial habitats in the soil is primarily important for revealing the mechanism of change of bacterial and fungal diversity and composition in the whole soil.…”
Section: Introductionmentioning
confidence: 99%